(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In India the term ―Healthcare‖ is usually associated with hospitals, but comprise of multipleaspects like pharmaceuticals, Hospitals, diagnostic Centres, ancillary centers, Health insurance,Telemedicine Healthcare software, medical tourism and medical equipment India‘s Healthcare Sectorpresents a not-so-healthy paradox as it is supposed to be. Indian Healthcare sector has not attempted fullyto make it competitive. The healthcare sector in India is booming thanks to rising governmental andprivate investment as well as increased access and usage. The aim of this study to overview of machinelearning based models to improve the healthcare sector. In the present scenario, it is essential toleverage machine learning techniques to provide affordable and easily accessible healthcare facilities inIndia.